Mass-spectrometry of extracts of young rats’ hearts via MALDIToF - Rohoza, L.A.; Чиж, М.О.; Halchenko, S.Ye.; Sandomirsky, B.P.; Gromovoy, T.Yu. (Dutch Peptide Symposium Lelystad, Netherlands. – 3 june 2016. P. 51., 2016)
Mass-spectrometry of extracts of young rats’ hearts via MALDIToF
Rohoza L.A., Chizh M.O., Halchenko S.Ye., Sandomirsky B.P., Gromovoy T.Yu. Mass-spectrometry of extracts of young rats’ hearts via MALDIToF. Dutch Peptide Symposium Lelystad, Netherlands. – 3 june 2016. P. 51.
Keywords: Mass-spectrometry